Optimization of Service Factors in PPI Tanjung Limau Bontang in Supporting Fishing Activites - Anggi, Anggi; Abdusysyahid, Said; Pagoray, Henny; Asikin, Andi Noor; Fitryana, Fitryana; Syahrir R, Muhammad (Hasanuddin University, 2023)
Utilization and optimization of service facilities at the PPI Tanjung Limau Bontang in supporting fishing businesses and strategies for developing service facilities in increasing fishing business activities that utilize the PPI Tanjung Limau Bontang. In this regard, an analysis is carried out to achieve priority alternative strategies. So that the achievement of service optimization can be carried out properly and sustainably. The aim of the study was to analyze the optimization of the utilization of available facilities and to analyze the strategy for optimizing the PPI Tanjung Limau to be applied in developing services under current conditions. the results of calculating the optimal utilization of service facilities, namely the TPI Building, Mooring Pier, Port Administration Office, Meeting Hall, Guard Post, IPAL, Kiosk or Shop and Parking Area. Meanwhile, service facilities whose utilization rate is not optimal are land 87%, Wharf unloading 50%, SPBN 80%, clean water tank 66.67%, electrical installation 20.67%, MCK (toilet) 66.67%, shipping lanes 65, 38% and anchorage pond 19.43%. The results of the SWOT analysis showed that the coordinate X value on the Cartesius diagram 0.77 and the coordinate Y 0.36 and the implementation of the strategy S-O (Strength-opportunity).